Tobacco production under global climate change: combined effects of heat and drought stress and coping strategies - Liu, Ming; Liu, Xianglu; Song, Yuxiao; Hu, Yanxia; Yang, Chengwei; Li, Juan; Jin, Shuangzhen; Gu, Kaiyuan; Yang, Zexian; Huang, Wenwu; Su, Jiaen; Wang, Longchang (Frontiers in Plant Science, 2024)
With the intensification of global climate change, high-temperature and drought stress have emerged as critical environmental stressors affecting tobacco plants' growth, development, and yield. This study provides a comprehensive review of tobacco's physiological and biochemical responses to optimal temperature conditions and limited irrigation across various growth stages. It assesses the effects of these conditions on yield and quality, along with the synergistic interactions and molecular mechanisms associated with these stressors. High-temperature and drought stress induces alterations in both enzymatic and non-enzymatic antioxidant activities, lead to the accumulation of reactive oxygen species (ROS), and promote lipid peroxidation, all of which adversely impact physiological processes such as photosynthetic gas exchange, respiration, and nitrogen metabolism, ultimately resulting in reduced biomass, productivity, and quality. The interaction of these stressors activates novel plant defense mechanisms, contributing to exacerbated synergistic damage. Optimal temperature conditions enhance the activation of heat shock proteins (HSPs) and antioxidant-related genes at the molecular level. At the same time, water stress triggers the expression of genes regulated by both abscisic acid-dependent and independent signalling pathways. This review also discusses contemporary agricultural management strategies, applications of genetic engineering, and biotechnological and molecular breeding methods designed to mitigate adverse agroclimatic responses, focusing on enhancing tobacco production under heat and drought stress conditions.